2021
DOI: 10.4103/jpbs.jpbs_761_20
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Results of Scanning Technique on Assessing Cement Thickness and Interfacial Nanoleakage of Luted CAD/CAM-fabricated Fiber Posts

Abstract: Background: Fiber posts are broadly used due to their good esthetics and elasticity close to that of dentin, which allows for uniform stress distribution within a root and lowers the possibility of nonrestorable root fractures. Aim and Objectives: The study assessed the layer of cement thickness and interfacial nanoleakage of luted fiber posts which were fabricated with CAD/CAM technology following direct scanning of the post space (DS) method, scanning of a polyether i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The mean ± standard deviation of cement distance was 154 ± 67 µm. These results are within the previously reported results obtained by Tsintsadze et al 15 who studied the effects of scanning technique on the performance of CAD/CAM-fabricated fiber posts and found that the cement thickness was 162 ± 24 μm for posts fabricated by the direct scanning of the post space, also within the results of Vaddamanu et al 16 who assessed the layer of cement thickness and nano leakage of luted fiber posts which were fabricated with CAD/CAM technology and recorded 172 ± 39 μm cement thickness of the milled posts fabricated using the direct technique.…”
Section: Table 1 Descriptive Statistics Of Cement Distance and Voids ...supporting
confidence: 91%
See 1 more Smart Citation
“…The mean ± standard deviation of cement distance was 154 ± 67 µm. These results are within the previously reported results obtained by Tsintsadze et al 15 who studied the effects of scanning technique on the performance of CAD/CAM-fabricated fiber posts and found that the cement thickness was 162 ± 24 μm for posts fabricated by the direct scanning of the post space, also within the results of Vaddamanu et al 16 who assessed the layer of cement thickness and nano leakage of luted fiber posts which were fabricated with CAD/CAM technology and recorded 172 ± 39 μm cement thickness of the milled posts fabricated using the direct technique.…”
Section: Table 1 Descriptive Statistics Of Cement Distance and Voids ...supporting
confidence: 91%
“…Void formations decrease the bonding strength by restricting the available area for cementation. 16 The prefabricated posts (RF group) showed the least voids volume and voids area between groups in all sections. This result disagrees with the result obtained by Gama et al 10 who used microcomputed tomography scanning to compare the voids volume of CAD/CAM milled glass fiber posts and prefabricated fiber posts in flared root canals and concluded that CAD/CAM Mansoura Journal of Dentistry Abdo et al…”
Section: Table 1 Descriptive Statistics Of Cement Distance and Voids ...mentioning
confidence: 87%
“…However among all other dental ceramics zirconia has the highest mechanical characteristics. In spite of superior mechanical properties, ceramics are brittle in nature to overcome the brittle nature of ceramics, resins are incorporated to increase the material's flexibility (6,7).These resin matrix ceramics can be classified as resin based ceramics and hybrid ceramics. The resin-based ceramics consist of polymer matrix with at least 80% nano sized ceramic filler particles whereas the hybrid ceramics made of a ceramic network infiltrated with a polymer(8).…”
Section: Introductionmentioning
confidence: 99%